Leverage and firm performance: Empirical evidence from Indian food processing industry - Sasikanta Tripathy (Management Science Letters, 2019)
The current study examines the association between financial performance and leverage for 56 food processing firms listed in BSE over the period 2000-2018 using pooled OLS, fixed effects, and random effects models. The results indicate that leverage was significantly and positively associated with the firm performance. The results obtained are thus robust across the estimation methods. The pecking order theory and the static trade-off theory, both seem to explain Indian food processing firms’ decisions among the alternative theories of capital structure.